Treatment with the glucagon receptor antagonist LY2409021 increases ambulatory blood pressure in patients with type 2 diabetes. Issue 8 (27th March 2017) - Kazda, Christof M.; Frias, Juan; Foga, Irene; Cui, Xuewei; Guzman, Cristina B.; Garhyan, Parag; Heilmann, Cory; Yang, Jihui Anne; Hardy, Thomas A.
Abstract : Aims: To assess the effect of LY2409021 on systolic blood pressure (SBP) in patients with type 2 diabetes. Materials and methods: This 6‐week, randomized, crossover study evaluated the effects of once‐daily administration of LY2409021 20 mg vs those of placebo on SBP, diastolic BP (DBP), and mean arterial pressure (MAP) using 24‐hour ambulatory BP monitoring (ABPM) in 270 subjects treated with diet/exercise ± metformin. Other measures included changes in glycemic control, serum lipids, and hepatic safety markers. Results: At 6 weeks of LY2409021 treatment, 24‐hour mean SBP was increased, with a least squares mean (LSM) difference of 2.26 mm Hg vs placebo (95% CI: 1.11, 3.40; P  < .001). The 24‐hour mean DBP and MAP also increased, with LSM differences of 1.37 mm Hg (95% CI: 0.66, 2.08; P  < .001) and 1.67 mm Hg (95% CI: 0.86, 2.47; P  < .001) vs placebo, respectively. At week 6, LY2409021 treatment reduced glycated hemoglobin (HbA1c) levels, with an LSM difference of −0.49% (−5.4 mmol/mol) (95% CI: −0.56%, −0.42% [−6.1, −4.6 mmol/mol]; P  < .001) vs placebo. Mean HbA1c at baseline was 7.3% (56 mmol/mol). Small but significant changes in serum lipid and aminotransferase levels were observed with LY2409021 treatment (all P  < .05 vs placebo). Conclusions: Statistically significant increases in BP, MAP and serum lipid levels were observed with LY2409021 treatment at a dose that lowered HbA1c and glucose levels. These effects may limit the clinical utility of LY2409021 as a chronic treatment for type 2 diabetes.